2013
DOI: 10.1111/jocn.12259
|View full text |Cite
|
Sign up to set email alerts
|

Perceived emotional intelligence in nursing: psychometric properties of the Trait Meta‐Mood Scale

Abstract: Use of the Trait Meta-Mood Scale in the nursing context would provide information about nurses' perceived abilities to interpret and manage emotions when interacting with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 58 publications
7
43
0
7
Order By: Relevance
“…A recent study of qualified and student nurses in Spain by Aradilla‐Herrero et al . () likewise found that clarity and mood repair were factors related to a reduction in death anxiety.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A recent study of qualified and student nurses in Spain by Aradilla‐Herrero et al . () likewise found that clarity and mood repair were factors related to a reduction in death anxiety.…”
Section: Discussionmentioning
confidence: 82%
“…More recently, the factor structure of the latter instrument was confirmed in a sample of nursing students (Aradilla‐Herrero et al . ). The Spanish adaptation of the scale, the TMMS‐24 contains 24 items that are rated on a five‐point Likert scale from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, only if professionals are able to manage the impact of these situations will they be able to offer the high‐quality care that patients deserve (Aradilla‐Herrero et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Esto también es concordante con algunos estudios (15,16,26). Estos resultados, junto con otras evidencias (25,27,38), orientan a que el factor más significativo que predice un cambio favorable en las actitudes hacia el cuidado al final de la vida es la formación temprana en actitudes hacia la muerte y el morir.…”
Section: Discussionunclassified